2017
DOI: 10.1186/s13054-017-1750-x
|View full text |Cite
|
Sign up to set email alerts
|

The future of mechanical ventilation: lessons from the present and the past

Abstract: The adverse effects of mechanical ventilation in acute respiratory distress syndrome (ARDS) arise from two main causes: unphysiological increases of transpulmonary pressure and unphysiological increases/decreases of pleural pressure during positive or negative pressure ventilation. The transpulmonary pressure-related side effects primarily account for ventilator-induced lung injury (VILI) while the pleural pressure-related side effects primarily account for hemodynamic alterations. The changes of transpulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
172
1
42

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(216 citation statements)
references
References 75 publications
1
172
1
42
Order By: Relevance
“…Mechanical ventilation is still the most important supportive treatment in patients with ARDS. Lung ventilation is the dynamic process of breathing to drive gases in and out the lungs [18]. During the mechanical ventilation treatment in ARDS, improper ventilator settings or excessive spontaneous breathing can cause ventilator-related damage, aggravate disease progression, and increase mortality [19].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical ventilation is still the most important supportive treatment in patients with ARDS. Lung ventilation is the dynamic process of breathing to drive gases in and out the lungs [18]. During the mechanical ventilation treatment in ARDS, improper ventilator settings or excessive spontaneous breathing can cause ventilator-related damage, aggravate disease progression, and increase mortality [19].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the development of MP was shown to be related to mortality in patients on mechanical ventilation, which included all aspects of ventilator parameters [14]; however, in our study, the discrimination of MP was also lower than that of LHPI. This result might be related to the MP itself still having some problems [22], such as the power not normalizing [31], the lack of ascertainment of the impact of MP throughout the lung, and the effect of expiratory phase on MP [32]. In our study, we observed that LHPI played a relatively important role in the random forest model.…”
Section: Discussionmentioning
confidence: 69%
“…Patients with elevated LHPI usually have high DP and low MAP. DP is the surrogate for cyclic lung strain [20], and high DP indicates excessive tidal volume and lung strain relative to "baby lungs," resulting in VILI [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in intra-abdominal pressure (IAP) affects lungs [4,5] producing atelectasis [6], impaired function [7] and, indirectly, inflammation and edema [8]. On the other side, an increase in thoracic pressure due to MV [9] may have an effect on inflammation and edema in the abdominal compartment. In fact, the decrease in venous return related to high positive end-expiratory pressure (PEEP) ventilation [10] has been well described.…”
Section: Introductionmentioning
confidence: 99%